A Cross Sectional Study on Drug Adherence among Type 2 Diabetes Mellitus Patients Attending a Tertiary Care Hospital in Chennai (Indian Journal of Public Health Research & Development, 2020)
Background: Diabetes Mellitus (DM), pose a major public health problem. With the fact of increasingburden of DM and its complications, it is essential to take measures to control blood glucose levels amongpatients. Adherence to medicine plays a vital role in maintaining the blood glucose level, hence the studywas planned to assess the drug adherence among type 2 DM patients attending a tertiary care hospital inChennai and to assess the factors associated with non-adherence in these patients.Method: Ninety three participants with Type 2 DMattending a tertiary care center were selected bysystematic random sampling method. Type 1 DM and Gestational DM patients were excluded. A semistructuredinterview with particulars about socio-demographic, clinical characteristics and adherence scorestool were used to collect the data. Data entry and analysis was done using SPSS version 20.Results: Mean age of participants was 54 ± 8.5 years. Sixty six percent of the participants were found tobe adherent to their diabetic medications. Common reason for non-adherence was found to be forgetfulness49.5%. Patients with DM for more than 5 years and patients not following regular physical activity werelikely to be non adherent. Patients with family support were more adherent.Conclusion: In spite of several public health measures, adherence level to medications was not satisfactory.The results emphasize the need to educate the patients about complications of DM and importance ofadherence to medication. Further,programme should encourage family support by educating the familymembers during home visits by health workers.
Keywords: Diabetes mellitus, Adherence, medication, factors, non- adherence